Developing Students’ Critical Thinking Skills Through Differentiated Problem-Based Learning - Hastuti, Karunia Puji; Arisanty, Deasy; Basuki, Sunarno; Dharmono, Dharmono; Rachman, Ali (Pedagogika, 2024)
This study aims to analyse critical thinking skills through differentiated problem-based learning (PBL). The data analysis methods included descriptive analysis, normality tests, homogeneity tests, independent sample t-tests, N-Gain, and ANOVA. The results of the research explain that PBL with differentiated instruction effectively improves students critical thinking skills and a significant effect of learning models and learning styles on students critical thinking skills.